ANALISIS SENTIMEN WARGANET TERHADAP GERAKAN BDS (BOYCOTT, DIVESTMENT AND SANCTIONS) PRODUK-PRODUK ISRAEL - Aditya Dimas Pratama; Pribadi, Kukuh (Universitas Muhammadiyah Jember, 2024)
The BDS Movement, a non-violent movement to pressure Israel against its violence against the Palestinian people, has become a massive cyber movement involving many social media accounts and other online mass media. Using the Brand24 Social Media Monitoring Tools, the researchers tried to read the sentiment that emerged around this topic, from the results of their analysis can draw the conclusion that the reach of the BDS Movement has been quite broad even though it has occasionally experienced rises and falls in terms of its reach. In addition, it was also found that 90% of citizens were negative about the topic and 10% were positive or neutral.